Cynicism and Nihilism - Gutauskas, Mintautas (Religija ir kultūra, 2012)
This article compares cynicism and nihilism, based on their ontological premises. One can notice that they are frequently considered as identical in the public discourse; indeed, they seem similar due to their relationship with morality and values; they both exercise negation and unmasking. However, it can be proven that they differ in terms of their ontological premises: while cynicism is based on the cynical realism, which is constituted in the perspective of the naked truth, nihilism is a form of thinking, which annihilates the possibility of realism itself and extinguishes the distinction between reality and illusion. Both of them are also compared from the aspect of reflexivity: nihilism is shown as a reflective thinking, while cynicism turns out to be a “practical” thinking without self-reflection. Finally, it is shown that although the truth of both nihilism and cynicism is enrooted in performativity, it is constituted differently by the way of unmasking.
Keywords: cynicism; nihilism; realism; Nietzsche